ANALISIS KEDUDUKAN HARTA WARISAN TERHADAP PELAKU PRAKTIK PERKAWINAN POLIGAMI - Imanda Afriliya, Dwi; Agam Illahi, Diki; Cahya Satriyani Putri, Carmel; Agus Setiawan, Valen; Widhantara, Endrian; Mul Erowati, Eti (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
Law Number 1 of 1974 requires approval from the Religious Court for polygamy, guided by Islamic principles in Q.S an-Nisa’ (4): 3 and (4): 129. This study aimed to explore inheritance distribution in polygamous marriages through a literature study with a juridical-normative approach and qualitative analysis. The findings showed that inheritance must be fairly distributed according to Islamic law. According to Section 96 (1) of the Compilation of Islamic Law (KHI), the surviving partner is entitled to half of the joint assets if death leads to divorce. If there are no children, the surviving husband receives half of his deceased wife’s assets, while with children, he receives a quarter. A wife inherits half of her husband’s estate if he dies without children and one-eighth if children are present. In polygamous marriages, only legitimate children from the marriage are recognized as heirs. This protects children’s inheritance rights, as affirmed by Article 42 of the Marriage Regulations and Article 99 of KHI, and supported by the Constitutional Court, ensuring the protection of children’s rights as heirs in both registered and unregistered polygamous marriages.